The value of the theoretical heritage of M. D. Kondratiev in the state regulation of the economy - O.O. Krynytska; T.I. Tkachuk (Економіка, управління та адміністрування)
The article considers the system of scientific views of the outstanding economist M.D. Kondratiev. Emphasis is placed on the causal link between the creation of the «long wave» theory and Kondratiev's interest in the problems of combining the market and the plan, the problems of prediction and forecasting. M.D. Kondratiev's original contribution to the development of the theory of cyclicity is shown, in particular, the inclusion of the time factor in cyclical factors, the division of economic processes into unique and inverse, the formulation of «correctness» of large cycles, the separation of innovations from discoveries, attention to technological progress. The problems of economic cyclicality are considered in terms of economic dynamics, as a violation of macroeconomic proportion. In addition, the practical significance of theory of cyclicity for predicting the violation of economic proportions and their timely solution at the lowest cost are shown. The analysis of the most important disproportions in different major business cycles is carried out and the reasons for their changes are revealed. The article analyzes the regularities of large cycles of conjuncture with the use of historical events that took place during separate cycles in scientific, political, social, industrial, monetary, geopolitical and other spheres. The contribution of M.D. Kondratiev is emphasized to the developments of the theory of state regulation of the economy, which he began studying in the 20s of the twentieth century, ie before J.Keynes, creating the concept of optimal planning. The originality and relevance of the theoretical heritage of M.D. Kondratiev is emphasized on the basis of the methodical approaches due to which it is possible to analyze the modern processes of economic development, in particular the modern big cycle of conjuncture. Its main feature was the transformation of the state into an active, often determining factor of cyclical processes and a generator of transformations and innovations, which actively uses the opportunities provided by a certain phase of the cycle. The scientific heritage of M.D. Kondratiev lies in the possibility and urgent need for its practical use in the process of public administration of socio-economic development. The days when the state only reflexively responded to challenges are gone. These challenges should be forecasted, the creation of protectors and plans, and the programs which were suggested and left to us by the prominent economist through his works.